Mrc1 (MMR, CD206) controls the blood proteome in reducing inflammation, age-associated organ dysfunction and mortality in sepsis - Damien Restagno; Mayank Saraswat; Peter V. Aziz; Kathryn Smith; Amanda J. Roberts; John Hintze; Jamey D. Marth (Nature Communications)
Abstract Circulating blood proteins and enzymes are maintained within normal physiological and clinically relevant concentration ranges. Excursions from normality include diagnostic markers and causes of disease. Rapid and persistent changes in the levels and functions of circulating blood components can reflect the functions of multiple endocytic lectin receptors. The majority of non-albumin blood proteins are post-translationally modified with sialylated N-glycans bearing cryptic ligands of various endocytic lectin receptors. During time in circulation, these cryptic ligands are progressively unmasked thereby contributing to glycoprotein half-life and abundance. The relationships between distinct lectin receptors and their endogenous ligand repertoires are not easily established. Herein we apply a glycosidic linkage enrichment strategy to identify accumulating mannosylated plasma glycoproteins linked to the absence of the endocytic Mrc1 (MMR, CD206) mannose-binding lectin receptor. We find that Mrc1 controls the abundance of over two hundred circulating endogenous mannosylated proteins in healthy mice at steady state, including glycoproteins linked to inflammation, age-associated organ dysfunction, and elevated mortality in sepsis. Increased circulating Mrc1 levels previously ascribed to proteolysis during sepsis are proportional to mannosylated protein accumulation in the blood. Assignment of circulating mannosylated proteins to curated biological and pathogenic signaling pathways reveals significant overlap between Mrc1 dysfunction and human sepsis.